2018
DOI: 10.3390/nu10030371
|View full text |Cite
|
Sign up to set email alerts
|

Looking through the Keyhole: Exploring Realities and Possibilities for School Breakfast Programs in Rural Western Australia

Abstract: Objective: To assess the school breakfast program (SBP) in two schools with high Aboriginal student populations in rural Western Australia, their contribution to holistic support, nutritional health education and possibilities for improvement. Methods: The operations and functioning of one regional and one remote SBP were assessed by stakeholder inquiry related to process and challenges, observations and documentary review. An intervention to increase health education, social interaction and learning about nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Three studies reported on programs or interventions that occurred in schools. One reported on an inschool breakfast program (Ichumar et al 2018). This program was largely a food distribution project, rather than a program aimed at increasing nutrition, however, this research identified several ways that nutrition and education activities could be incorporated into breakfast programs.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Three studies reported on programs or interventions that occurred in schools. One reported on an inschool breakfast program (Ichumar et al 2018). This program was largely a food distribution project, rather than a program aimed at increasing nutrition, however, this research identified several ways that nutrition and education activities could be incorporated into breakfast programs.…”
Section: Resultsmentioning
confidence: 98%
“…Table two about here Most articles (n=18) reported on cross-sectional studies (Abbott et al 2010, Abbott et al 2012, Adams et al 2012, Brown et al 2019, Ferguson et al 2017b, Foley et al 2011, Gooey et al 2017, Hume et al 2013, Hume et al 2014, Ichumar et al 2018, Magnus et al 2018, Magnus et al 2016, Murray et al 2014, Porter et al 2011, Reilly et al 2011, Rogers et al 2018, Viola 2006, six were longitudinal (Black et al 2014, Brimblecombe et al 2017a, Brimblecombe et al 2014, Brimblecombe et al 2015, Burrows et al 2015, and one was a randomised controlled trial (Brimblecombe et al 2017b). Nine studies employed more than one method for data collection (Adams et al 2012, Black et al 2014, Brimblecombe et al 2017a, Brown et al 2019, Burrows et al 2015, Ferguson et al 2017b, Ichumar et al 2018, Reilly et al 2011, 20 employed qualitative methods (Abbott et al 2010, Abbott et al 2012, Brimblecombe et al 2014, Brimblecombe et al 2015, Foley et al 2011, Hume et al 2013, Murray et al 2014, Porter et al 2011, Rogers et al 2018, Viola 2006, two were economic evaluations…”
Section: Resultsmentioning
confidence: 99%
“…A school is a convenient setting to implement peer-led interventions as many interactions take place between school children. Examples of nutrition interventions in school settings with Indigenous students include the implementation of nutrition education in the curriculum [18], the introduction or improvement of breakfast/lunch programs [18,33], the introduction of cooking classes [22], culturally appropriate physical activities [16], and a change in provisions of the school canteen [34], which may supplement general healthy nutrition programs such as the National Healthy School Canteen (NHSC) guidelines and resources, state-level Healthy Food and Drink policies and other initiatives like Crunch ’n Sip which are run in schools [33,35,36].…”
Section: Resultsmentioning
confidence: 99%
“…Social benefits included relationship building, cross-generational interaction, school engagement, the development of manners and skills, and monitoring student well-being. Some of these social benefits have been previously identified (Byrne et al, 2018; Defeyter, Graham, & Prince, 2015; Graham et al, 2015; Ichumar et al, 2018) with attendance at SBCs improving children’s self-reported friendship quality and reducing experience of peer victimization (Defeyter, Graham, & Russo, 2015). In our study, a few children described negative interpersonal experiences, but the majority spoke positively about their socialization.…”
Section: Discussionmentioning
confidence: 96%